Analysis of Static and Dynamic Characteristic of a Transfer Gearbox based on Finite Element - Xue Song; Yu Cungui; Xu Zuguo (Jixie chuandong)
For improvement of the transmission accuracy and static and dynamic characteristics of a transfer gearbox of a test-bed. By using the finite element software Abaqus,a numerical calculation model can be established to make static and dynamic characteristics analysis. Firstly,by making static analysis of typical working condition based on finite element,the condition of stress and deformation is achieved to check the static reliability of its structure. Then,the possibility of resonance under the normal working conditions is ascertained by using modal analysis. The purpose of this is to provide theoretical basis and guidance for the following structural optimization design. Research shows,the gearbox is reliable in structure and has a great space for optimization.The structural optimization can be used to improve the transmission accuracy and static and dynamic characteristics.